Intra-articular vs. intravenous administration: a meta-analysis of tranexamic acid in primary total knee arthroplasty - Jin Li; Ruikang Liu; Saroj Rai; Renhao Ze; Xin Tang; Pan Hong (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The optimal dosage and administration approach of tranexamic acid (TXA) in primary total knee arthroplasty (TKA) remains controversial. In light of recently published 14 randomized controlled trials (RCTs), the study aims to incorporate the newly found evidence and compare the efficacy and safety of intra-articular (IA) vs. intravenous (IV) application of TXA in primary TKA. Methods PubMed, Embase, Web of Science, and Cochrane Library were searched for RCTs comparing IA with IV TXA for primary TKA. Primary outcomes included total blood loss (TBL) and drain output. Secondary outcomes included hidden blood loss (HBL), hemoglobin (Hb) fall, blood transfusion rate, perioperative complications, length of hospital stay, and tourniquet time. Result In all, 34 RCTs involving 3867 patients were included in our meta-analysis. Significant advantages of IA were shown on TBL (MD = 33.38, 95% CI = 19.24 to 47.51, P < 0.001), drain output (MD = 28.44, 95% CI = 2.61 to 54.27, P = 0.03), and postoperative day (POD) 3+ Hb fall (MD = 0.24, 95% CI = 0.09 to 0.39, P = 0.001) compared with IV. There existed no significant difference on HBL, POD1 and POD2 Hb fall, blood transfusion rate, perioperative complications, length of hospital stay, and tourniquet time between IA and IV. Conclusion Intra-articular administration of TXA is superior to intravenous in primary TKA patients regarding the performance on TBL, drain output, and POD3+ Hb fall, without increased risk of perioperative complications. Therefore, intra-articular administration is the recommended approach in clinical practice for primary TKA.